Reanalysis of Mitochondrial and Nuclear Markers (COI, 16S, 28S) in Coenobitidae, Diogenidae, and Paguridae for Species Delimitation - Tazkiah Auliaputri; Tyani Fitrian; Achmad Alfiyan; Intan Ratu Pratiwi; Vendi Eko Susilo; Ali Mashar; Achmad Farajallah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2026)
Public sequence repositories, such as GenBank, contain an extensive collection of molecular data that are widely used for phylogenetic inference and species identification. However, inconsistent annotation and potential misidentifications can obscure true genetic patterns, particularly in groups with complex morphology such as Paguroidea. This study reanalyzed 4,871 COI, 16S, and 28S sequences belonging to the families Coenobitidae, Diogenidae, and Paguridae retrieved from GenBank. Following rigorous quality filtering, 2,450 sequences were retained for downstream analyses to quantify intra and interspecific genetic distances for each family and each molecular marker. The results reveal substantial heterogeneity in genetic divergence across families, with COI and 16S exhibiting broad ranges and frequent overlap between intra and interspecific distances, whereas 28S displayed very low variation consistent with its slower evolutionary rate. Elevated intraspecific distances in several taxa suggest potential cryptic lineages, while unusually shallow interspecific values indicate possible synonymy or recent divergence. Rather than proposing taxonomic changes, this study provides a curated reference framework that establishes empirical distance thresholds for molecular species delimitation in Paguroidea. These findings offer a practical baseline for future research employing COI, 16S, and 28S markers in species identification, validation of public sequence data, and the refinement of hermit crab systematics.